Exposure to heat-inactivated Trichophyton rubrum resulting in a limited immune response of human keratinocytes - HUANG, Xiao-qiang; YI, Jin-ling; YIN, Song-chao; CHEN, Rong-zhang; LI, Mei-rong; GONG, Zi-jian; LAI, Wei; CHEN, Jian (Chinese medical journal, 2013)
Background Trichophyton rubrum （T. rubrum） represents the most important agent of dermatophytosis in humans. T. rubrum infection causes slight inflammation, and tends to be chronic and recurrent. It is suggested that it may result from the failure of epithelial cells to recognize T. rubrum effectively and initiate effective immune responses. The C-type lectin receptors （CLR） and toll-like receptors （TLR） are the two major pattern recognition receptors （PRRs） that recognize fungal components. Therefore, the purpose of the study was to analyze the expression of those PRRs and the cytokines in HaCaT cells stimulated with heat-inactivated T. rubrum conidia and hyphae, respectively. Methods HaCaT cells were unstimulated or stimulated with heat-inactivated T. rubrum conidia and hyphae （l×106 and 1.5×105 colony-forming unit （CFU） in 2 ml medium, respectively） for 6, 12 and 24 hours. The mRNA expression of PRRs involved in recognizing fungal pathogen-associated molecular patterns （PAMPs） and signaling molecules were measured by quantitative reverse transcription polymerase chain reaction （RT-PCR）. Meanwhile, surface toll-like receptor （TLR） 2, TLR4 and Dectin-1 were analyzed by fluorescence-activated cell sorter （FACS） 24 hours after treatment. The cytokines were detected in cell culture supernatants of HaCaT cells in 12 and 24 hours after treatment. Results HaCaT cells constitutively expressed mRNA of membrane-bound TLR1,2, 4 and 6, Dectinl and DC-SIGN, but not Dectin-2 or Mincle. Heat-killed T. rubrum did not significantly upregulate gene transcriptions of the PRRs of HaCaT cells. Heat-inactivated T. rubrum conidia significantly reduced the surface expression of TLR2 and Dectin-1, and suppressed the secretions of interferon-inducible protein-10 （IP-10） and monocyte chemotactic protein-1 （MCP-1） of HaCaT cells, while heat-killed T. rubrum hyphae significantly induced the secretions of IP-10 and MCP-I. Conclusion The cell-wall antigens of T. rubrum fail to activate transcriptional expression of PRRs and induce a lower immune response of HaCaT cells by limited cytokines secretion.